Appealing to Tacit Knowledge and Axiology to Enhance Medical Practice in the COVID-19 Pandemic: A Systematic Review and Hermeneutic Bioethical Analysis - Ana-Beatriz S; Ana-Beatriz S; Ana-Beatriz S; Myriam M. Altamirano-Bustamante; Myriam M. Altamirano-Bustamante (Frontiers Media S.A., 2021)
Background: The pressure of coronavirus disease 2019 (COVID-19) pandemic, epidemiological and demographic changes, personnel-patient relationship in healthcare, and the development of biotechnologies do not go unnoticed by the healthcare professional. Changes are so wide and at a high rate that guidelines and mere scientific knowledge, which are represented by evidence-based medicine, are not sufficient to lead actions, thus the experiential aspects in the configuration of an ethos present as a fundamental part of the resources to deal with critical scenarios, such as a pandemic. In this regard, the recognition of tacit knowledge as a way of teaching and learning skills related to ethical aspects such as principles, virtues, and values, revealed as a fundamental part of the clinical field. The challenge is to strengthen binomial evidence-based medicine and values-based in order to achieve excellence in the health care of the patients and the well-being of the clinical personnel.Method: A 2-fold analysis was conducted taking pediatric endocrinology as an example. First, a systematic review was carried out in electronic databases BIREME, PubMed, and PhilPapers following PEO and PRISMA approaches. A total of 132 articles were garnered. After reading their title and abstract, 30 articles were obtained. Quantitative information was arranged in an Excel database according to three themes: ethics, axiology, and tacit knowledge. A quality criterion that meets our research question was assigned to each article and those which had a quality criterion of 3 (9) were taken to carry out the hermeneutic bioethical analysis, which consisted of three stages, namely naïve reading, codification, and interpretation. The results were analyzed in Atlas.ti. to elucidate the relations between the three main themes in accordance with the objective.Results: Although there was no difference in the frequency of tacit knowledge skills, including cognitive, social, and technical, for medical practice, there is an intrinsic relationship between epistemic and ethical values with cognitive skills, this means that professionals who practice honesty, authenticity and self-control are capable of seeing patients as persons and thus respect their dignity. This suggested that there is a strong partnership between evidence-based medicine and value-based medicine, which reinforced this binomial as the two feet on which medical practice decisions rested. With regard to tacit knowledge in terms of the context of the COVID-19 pandemic, the challenges refer to (1) adapting and learning a new way of establishing trust with the patient and (2) how to capitalize on the new knowledge that new experiences have posed.Discussion: The analysis of ethical-tacit knowledge in medicine is a recent phenomenon and is in full development. Although no references were found that dealt with any of the main topics in pediatric endocrinology, there is an interest in pediatrics to explore and discuss educational strategies in ethics related to its tacit dimension as a vector of enhancement in the clinical practice. Educational strategies ought to take into consideration the development of skills that promote reflection and discussion of experiences, even more vigorously in the context of the COVID-19 pandemic.